Comparison of the Total, Diazotrophic and Ammonia-Oxidizing Bacterial Communities Between Under Organic and Conventional Greenhouse Farming - Chen, Chen; Han, Hui; Xu, Ting; Lv, Yizhong; Hu, Kelin; Li, Xue Xian; Qiao, Yuhui; Ding, Guo-Chun; Li, Ji (Frontiers in Microbiology, 2020)
Organic greenhouse farming is an innovative system that may maintain a high yield and healthy agroecosystem. There have been no rigorous studies on the comparison of total and nitrogen-cycling bacterial community in vegetable soils between organic and conventional farming management at large scale. A survey of bacterial community and nitrogen cycles from soils under organic and conventional greenhouse farming was performed at 30 sites, covering seven soil types with four to eighteen years of organic farming history. Communities of the total, diazotrophs and ammonia-oxidizing bacteria were studied with high-throughput sequencing of the 16S rRNA, nifH and amoA genes, respectively. Organic greenhouse farming did not influence alpha diversities. Beta diversities among the total (26/30) and diazotrophic (17/19) bacteria differed between farming systems, but compositional differences in ammonia-oxidizing bacteria between the two farming systems were only detected at 6 sites. Despite the effects of farming system on most bacterial genera were varied across different sites, organic greenhouse farming persistently selected for a few genera, possibly for the biodegradation of organic carbon with high molecular weight (Hyphomicrobium, Rubinisphaera, Aciditerrimonas, Planifilum, Phaselicystis, Ohtaekwangia), but against putative ammonia oxidizing (Nitrosospira, Nitrosopumilus) and diazotrophic (Bradyrhizobium) bacterial genera, as determined by 16S rRNA analysis. Diazotrophic bacteria affiliated with nifH cluster 1J were preferentially associated with organic greenhouse farming, in contrast to Paenibacillus borealis. In summary, this study provides insights into the complex effects of organic greenhouse farming on the total, diazotrophic and ammonia oxidizing bacterial communities across different environmental context.